Penerapan Model Pembelajaran Game-Based Learning untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa pada Materi Gangguan Sistem Pernapasan Manusia - Reinelbi Esbi Pabetta; Anatje Lihiang; Masje Wurarah (Jurnal Cakrawala Pendidikan dan Biologi, 2026)
This study aims to improve student learning activeness and outcomes in eleventh-grade students at SMA Negeri 1 Kawangkoan Barat on the topic of respiratory system disorders through the implementation of the game-based learning (GBL) model. Low student achievement was attributed to passive participation, teacher-centered instruction, and insufficient student engagement during lessons. This study employed a Classroom Action Research (CAR) design executed over two cycles involving 21 students as research subjects. Each cycle comprised four stages: planning, action, observation, and reflection. Multiple-choice test items and observation sheets for student activities served as research instruments. Results showed an improvement in classical learning completeness from 76.19% in Cycle I (mean score: 85.24) to 91.30% in Cycle II (mean score: 88.76), representing an increase of 15.11%, which confirmed that the success criterion (≥85% students achieving mastery) was met. Observations of student activity also revealed an increase from the "Active" category in Cycle I (85.71% active students) to "Very Active" in Cycle II (86.96% active students). These findings demonstrate that the game-based learning model effectively enhances student biology achievement by promoting interactive learning, motivation, and collaborative problem-solving activities.